The first stage of the common market: report on the execution of the treaty - European economic community-commission (European economic community: Brussels, 1962)
This book explain some of the common day-to-day market principles.
Include appendix
asm; 25/01/19
Loans
Keywords: European Economic Community; European Economic Community